Antecedents of Passenger Loyalty in Online Taxi Services: A Case Study of GoCar Services - Kamal, Kevin; Sijabat, Rosdiana (Faculty of Economics and Business, Jenderal Soedirman University, 2023)
This research was conducted to determine the relationship between perceived value (X1), value for money (X2), corporate image (X3), and switching costs (X4) on passenger satisfaction (M) and passenger loyalty (Y) for GoCar customers in Indonesia. This research is a quantitative study using a questionnaire with statement items arranged using a Likert scale (1-5). The sampling technique was carried out using the Lemeshow formula for an unknown population. The data obtained was then processed using the PLS-SEM method with the SmartPLS 3.2.9 application. The results of the study found that perceived quality, value for money, and corporate image in the four-wheeled ride-hailing service industry affect passenger satisfaction which will then generate passenger loyalty. Switching costs were also found to positively affect passenger loyalty. This implies that four-wheeled ride-hailing customers care about quality, price and quality comparison, corporate image, and costs/barriers that arise when they decide to switch from a service.